NRF2 pathway activation by KEAP1 inhibition attenuates the manifestation of aging phenotypes in salivary glands - Sisca Meida Wati; Daisuke Matsumaru; Hozumi Motohashi (Redox Biology, 2020)
Saliva plays an essential role in the maintenance of oral health. The oral cavity environment changes during aging mainly due to alterations in the secretion and composition of saliva. In particular, unstimulated basal salivary flow decreases with age. The functional decline of the salivary glands impairs chewing and swallowing abilities and often becomes one of the predispositions for aging-related disorders, including aspiration pneumonia. The KEAP1-NRF2 system plays a central role in the regulation of the oxidative stress response. NRF2 is a transcription factor that coordinately regulates cytoprotective genes, and KEAP1 is a negative regulator of NRF2. Although NRF2 activation has been suggested to be advantageous for the prevention of aging-related diseases, its role in the course of physiological aging is not well understood. To investigate the impact of NRF2 activation on salivary gland aging, we compared the submandibular glands of Keap1-knockdown (KD) (Keap1FA/FA) mice in which NRF2 is activated with those of wild-type mice. Young mice did not show any apparent differences between the two genotypes, whereas in old mice, clear differences were observed. Aged wild-type submandibular glands exhibited iron and collagen depositions, immune cell infiltration and increased DNA damage and apoptosis accompanied by elevated oxidative stress, which were all markedly attenuated in Keap1-KD mice, suggesting that NRF2 activation has antiaging effects on salivary glands. We propose that appropriate activation of NRF2 is effective for the maintenance of healthy salivary gland conditions and for the prevention of hyposalivation in the elderly.